First steps into the discipline: On the 'spirit' in the discipline of Christian spirituality - Lombaard, Christo (HTS Teologiese Studies / Theological Studies, 2019)
In this article on entering the academic discipline of Christian Spirituality, terminological sensitivities in interdisciplinary work are taken as a point of departure. From this more general base, the following four points are argued: 'Spirituality' is a multivalence term, indicated from academic considerations and from non-academic writings of our time, with journalism serving as a productive example; terms 'spirit', 'spirituality' and 'Holy Spirit' ought not to be conflated with one another by new colleagues entering the discipline of Christian Spirituality; Christian Spirituality studies the experience-expression-dynamics of the Christian faith, and not the Holy Spirit as primary topic of investigation; however this should not be taken to imply an impoverished Christian theology, because the Trinity, as demonstrated, remains part of the core assumptions of this discipline.
Free
Keywords: 'Spirit'; CHRISTIAN spirituality; CHURCH discipline; Christian spirituality; Entering the discipline; HOLY Spirit; Holy Spirit; Inter-disciplinary; THEOLOGY